Correction: The Cyprus Institute of Neurology and Genetics, an emerging paradigm of a gender egalitarian organisation. - Stavroulla Xenophontos; Margarita Zachariou; Pavlos Polycarpou; Elena Ioannidou; Vera Kazandjian; Maria Lagou; Anna Michaelidou; George M Spyrou; Marios A Cariolou; Leonidas Phylactou (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0274356.].